Pengaruh Siklus Konversi Kas, Pertumbuhan Penjualan dan Ukuran Perusahaan Terhadap Cash Holding - Bella Nugraheni,; Cris Kuntadi,; Rachmat Pramukty, (Manajemen Kreatif Jurnal, 2023)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that influence cash holding, namely the cash conversion cycle, sales growth and company size, a study of financial management literature. The purpose of writing this article is to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are: 1) the cash conversion cycle has an effect on cash holding; 2) sales growth affects cash holdings; and 3) company size has an effect on cash holding.